Al-Muṣṭalaḥāt al-Siyāsiyyah fī al-Qur’ān al-Karīm Dirāsah Lughawiyyah Dalāliyyah Fiqhiyyah fi Ḍaw’ al-Lisāniyyāt al-Naṣṣiyyah - Khālid Khamīs Muṣṭafa Farrāj; Qusaiyen Qusaiyen (Islam Futura, 2020)
The study of the words of the Holy Qur’an and the formation of its terminology represent an origin of the language, given the constant of the affiliation of the Holy Qur’an to the heart of Arab life, and the beginning of its development. The Holy Qur’an is one of the Arab pilgrims, and its vocabulary, vocabulary and terminology is at the top of the ladder of eloquence. This study relied on the descriptive historical approach, followed by examples of political terms: peace and reconciliation, covenant and the Charter, and it was a semantic linguistic study, in the light of Quranic evidence, to differentiate the significance of these terms and their meanings, with reference to the semantic and use differences between those words.